PENGARUH MODEL SCIENTIFIC CRITICAL THINKING (SCT) TERHADAP SELF-EFFICACY DAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA BIOLOGI - Sembiring, Al Khudri; Eriyanti, Ribut Wahyu; Hudha, Atok Miftachul (Universitas Lancang Kuning, 2023)
A person's success in mastering a material is caused by the belief he has, because it is this belief that will cause a person to behave in such a way that the belief will materialize. One source of belief is the level of self-confidence. ability (self-efficacy). The Scientific Critical Thinking (SCT) model is a model that can be applied to material on the human respiratory system in class A1 and A2 biology lessons at Lancang Kuning University. This study aims to determine critical thinking skills, communication skills and self-efficacy of biology students in the application of the SCT model to the material on the respiratory system. The method in this study was a quasi-experimental study with a post-test nonequivalent control group design. The sample of this study were students in class A1 biology (experimental class) and class A2 biology (control class). Retrieval of data in research using test and non-test techniques. Data analysis techniques used in this study are descriptive and inferential. The results showed that (1) there was an increase in critical thinking skills (2) an increase in communication skills and (3) an increase in self-efficacy. The experimental class was better than the control class in training biology students' critical thinking skills, communication skills, and self-efficacy in learning material on the human respiratory system.